Geranylated Coumarins From Thai Medicinal Plant Mammea siamensis With Testosterone 5α-Reductase Inhibitory Activity - Morikawa, Toshio; Luo, Fenglin; Manse, Yoshiaki; Sugita, Hidemi; Saeki, Shunsuke; Chaipech, Saowanee; Pongpiriyadacha, Yutana; Muraoka, Osamu; Ninomiya, Kiyofumi (Frontiers in Chemistry, 2020)
Geranylated coumarin constituents, kayeassamin I (1) and mammeasins E (2) and F (3) were newly isolated from the methanol extract of the flowers of Mammea siamensis (Calophyllaceae) originating in Thailand, along with five known isolates such as mammea E/BC (23), deacetylmammea E/AA cyclo D (31), deacetylmammea E/BB cyclo D (32), mammea A/AA cyclo F (34), and mammea A/AC cyclo F (35). These compounds (1–3) were obtained as an inseparable mixture (ca. 1:1 ratio) of the 3''R and 3''S forms, respectively. Among the isolated coumarins from the extract, mammeasins E (2, 22.6 μM), A (4, 19.0 μM), and B (5, 24.0 μM), kayeassamins E (9, 33.8 μM), F (10, 15.9 μM), and G (11, 17.7 μM), surangin C (13, 5.9 μM), and mammeas A/AA (17, 19.5 μM), E/BB (22, 16.8 μM), and A/AA cyclo F (34, 23.6 μM), were found to inhibit testosterone 5α-reductase.